Malignant Ectopic Thymoma in the Neck: A Case Report - Jung, Jung Im; Kim, Hak Hee; Park, Seog Hee; Lee, Youn Soo (American Journal of Neuroradiology, 1999)
Summary: We report a case of malignant ectopic thymoma in the neck. Contrast-enhanced CT of the neck showed a well-defined inhomogeneously enhancing mass in the left jugulodigastric chain. One year after surgery, the mass had metastasized to the tongue base, and CT of the neck showed an ill-defined densely enhancing mass with lymphadenopathy.